Exploring Use of a Protein Cage System for Producing Bioactive Peptides in Escherichia coli - Maxim D. Harding; Mark A. Jackson; Edward K. Gilding; Kuok Yap; David J. Craik; Frank Sainsbury; Nicole Lawrence (Microbial Biotechnology)
ABSTRACT New therapeutics are urgently needed to curb the spread of drug‐resistant diseases. Bioactive peptides (BAPs), including antimicrobial peptides, are emerging as an exciting new class of compounds with advantages over current drug modalities, especially small molecule drugs that are prone to resistance development. Here, we evaluated a bacteriophage P22 virus‐like particle (VLP) system where BAPs are encapsulated as fusion proteins with the P22 scaffold protein (SP) within self‐assembling protein cages in Escherichia coli. Representative peptides from three structurally distinct classes of BAPs were successfully encapsulated into P22 VLPs at high cargo to VLP coat protein (CP) ratios that corresponded to interactions between the compact electropositive structures of the SP‐BAPs and electronegative regions on the inward facing surface of CP subunits. However, high loading densities did not correspond to improved SP‐BAP yields. An unexpected finding of this study was that while encapsulation alleviated negative effects of SP‐BAPs on E. coli growth, the P22 scaffold protein acted as a sufficient fusion partner for accumulating BAPs, and co‐expression of the CP did not further improve SP‐BAP yields. Nevertheless, encapsulation in VLPs provided a useful first step in the purification pipeline for producing both linear and cyclic recombinant (r)BAPs that were functionally equivalent to their synthetic counterparts. Further efforts to optimise expression ratios of CP to SP‐BAP fusions will be required to realise the full potential of encapsulation for protecting expression hosts and maximising rBAP yields.